Kh. Abdul Karim Jamak: His Tiological Perspective on Qada' and Qadar in the Digital Era at Kerinci Regency - Jambi - Ahmad Zuhdi; Fakhri Yusuf; Marwan Marwan (Dinasti Publisher, 2024)
This article explains the theme